Survey on the Basic Technical Skills of Fast Walking Athletes in Lahat Regency - Megariani, Evi; Handayani, Widya; Lestari, Hikmah (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This study aims to determine the essential technical skills of fast-walking athletes in Lahat Regency. This research uses quantitative descriptive research methods along with survey methods. The population for this study was all 13 speed-walking athletes who took part in training at the Regency Athletic Club. The sample in this research was 13 people, and the total sampling technique was used. Research data was collected using a fast-walking test. The data analysis technique used in processing research data is analyzed using descriptive statistical methods in the form of mean, mode, standard deviation, and coefficient of variance. The results showed that two athletes (15.38%) had the essential technical skills of fast-walking athletes in the outstanding category. Five athletes (38.46%) had the essential technical skills of fast-walking athletes in the excellent category, and 6 Athletes (46.15%) had the basic technical skills of fast-walking athletes in the poor category. It can be concluded that the basic technical skills of fast-walking athletes in Lahat Regency are still at a poor stage, so an analysis of the factors that influence the basic technical skills of fast-walking athletes is needed, and special training methods are also needed to improve the basic technical skills of fast walking athletes in Kabul. Lahat patent.